Ultrastrong interstitially-strengthened chemically complex martensite via tuning phase stability. (15th March 2023) - Wang, Shidong; Wang, Jinhua; Yang, Yong; Wang, Penghui; Zhang, Shubo; Liu, Junpeng; Guo, Zongchang; Luan, Hengwei; Zhang, Chi; Jiao, Zengbao; Yang, Zhigang; Sha, Gang; et al.
Abstract: Cantor alloy (Fe20 Co20 Cr20 Ni20 Mn20 ) and its derivatives, as the extensively studied chemically complex alloys (CCAs), exhibit remarkable ductility but relatively low strength due to face-centered cubic (fcc) matrix. By carefully tuning the phase stability of interstitial CCAs (iCCAs), we produced a lath-martensite matrix with a body-centered cubic (bcc) structure to achieve ultrahigh strengths. The iCCA with a martensite matrix (iCCM) displays an ultrahigh yield strength (YS) of ∼1.3 GPa, an ultimate tensile strength (UTS) of ∼ 1.9 GPa and a decent fracture elongation of ∼11 %. The thermally-induced martensitic transformation contributes to a remarkable YS increase, i.e., ∼ 1 GPa as compared with that of a fcc-iCCA, which provides an alternative strengthening route for CCAs without complex processing and profuse nanoprecipitates. This alloy design strategy combines the wide chemical composition space and potential advantages of CCAs and ultrahigh strength of bcc-martensite in steels, opening a new window to develop high-performance materials. Graphical abstract: Image, graphical abstract